Microarray expression profiles analysis revealed lncRNA OXCT1‐AS1 promoted bladder cancer cell aggressiveness via miR‐455‐5p/JAK1 signaling. Issue 8 (4th January 2019) - Chen, Jin‐Bo; Zhu, Ye‐Wen; Guo, Xi; Yu, Cui; Liu, Pei‐Hua; Li, Chao; Hu, Jiao; Li, Hui‐Huang; Liu, Long‐Fei; Chen, Min‐Feng; Chen, He‐Qun; Xiong‐Bing, Zu
Abstract: Bladder cancer (BCa) is one of the most prevalent cancers of the urinary system worldwide. Accumulating evidence suggests that long noncoding RNAs (lncRNAs) perform a vital function in the pathogenesis and progression of BCa. In the current study, we identified a novel lncRNA OXCT1‐AS1 and investigated its role and potential mechanisms in BCa. The microarray results showed the expression of lncRNAs, microRNAs, and messenger RNAs between BCa primary tumor tissues and metastatic lymph nodes were significantly different. The quantitative polymerase chain reaction verification was performed to ensure the reliability of the screening results. The Cell Counting Kit 8 and transwell assay were used to assess the tumor cell proliferation and invasion abilities in vitro, respectively. The dual‐luciferase activity assay was performed to investigate the potential mechanism of competing endogenous RNA network. lncRNA OXCT1‐AS1, which elevated in metastasis lymph node, was significantly upregulated in BCa cell lines compared with SVHUC‐1. We demonstrated OXCT1‐AS1 inhibited miR‐455‐5p to decrease its binding to the JAK1 3′‐untranslated region, which could upregulate the expression of JAK1 at the protein level, thus promoting BCa proliferation and invasion. Therefore, lncRNA OXCT1‐AS1 could act as a potential biomarker and therapeutic target for patients with BCa. Abstract : The microarray results showed the expression of long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and messenger RNAs (mRNAs) between bladder cancer (BCa) metastatic lymph nodes and primary tumor tissues were significantly different. lncRNA OXCT1‐AS1, which elevated in metastasis lymph node, was significantly upregulated in BCa cell lines compared with SVHUC‐1. We demonstrated OXCT1‐AS1 inhibited miR‐455‐5p to decrease its binding to the JAK1 3′‐untranslated region (UTR), which could upregulate the expression of JAK1 at the protein level, thus promoting BCa proliferation and invasion.